Patient and Caregivers' Perspectives on Biosimilar Use in Pediatric Inflammatory Bowel Disease. Issue 1 (20th April 2022) - Yossef, Lina; Wright, Molly; Benedict, Jason; Morris, Grant A.; McNicol, Megan; Boyle, Brendan; Dotson, Jennifer L.; Michel, Hilary K.; Maltz, Ross M.
Abstract : Background: Studies assessing adult inflammatory bowel disease (IBD) patient perspectives on biosimilar use revealed that most were unfamiliar with biosimilars and had a negative perception. The objective of this study was to evaluate the perspectives of pediatric patients with IBD and their caregivers regarding biosimilar use and non-medical switches. Methods: A survey was given to a cross section of patients with IBD ages 11–21 years receiving the intravenous anti-tumor necrosis factor originator and caregivers of patients with IBD ages 3–21 years receiving the originator. Recruitment occurred via mail, during clinic visits, and infusions. Fisher exact tests were used to test for statistically significant differences. Results: Response rate amongst caregivers was 49% (n = 98) and among patients was 35% (n = 67). Sixty-four percent of caregivers and 79% of patients had never heard of biosimilars. There was increased discomfort surrounding the use of biosimilars and switching to a biosimilar amongst caregivers who had previously heard of biosimilars compared to caregivers who had not previously heard of biosimilars ( P < 0.05). Similar concerns were not seen in patient respondents. The length of time on the originator had no effect on patient or caregiver concerns related to biosimilar efficacy, adverse effects, or switches. Conclusion: The majority of pediatric patients and caregivers had never heard of biosimilars. Caregivers that had heard of biosimilars before the study were more likely to have a negative perception of them. This study highlights the importance of providing thorough and accurate education to pediatric patients and families regarding the safety and efficacy of biosimilars.